Propuesta de producción más limpia para el aprovechamiento de agua de condensación de los aires acondicionados en la Universidad de la Costa (2019)
It is clear that the planet is facing a crisis of shortage of fresh water, therefore, it is important to explore the alternatives that are found in the water and the minimum cost. The idea of this research, which was reused, the condensed water, the air conditioners, as an alternative source, for uses, such as irrigation and cleaning, in block 7 of the Universidad de la Costa. Impact on saving resources. In this sense, the research will focus on characterizing and quantifying the generation of condensed water, in addition, a diagnosis of the water conditions of the block will be seen, and the viability of the proposal will be verified through the integral application of cleaner production tools. The methodology used in this research is of the quasi-experimental type, with a quantitative approach and an exploratory scope, so that information is scarce and is the starting point for future research. Through an initial review, information was obtained about the current conditions of block 7, as well as an equation and a cost-benefit analysis that allowed obtaining the viability of the proposal, as well as the financial and environmental benefits for the university. Finally, the characterization and generation of condensate water are acceptable in the use of cleaning and irrigation that meets the requirements established in Colombian regulations (Resolution 1207 of 2014 and 2115 of 2007).